Cadmium Exposure and Osteoporosis: A Population‐Based Study and Benchmark Dose Estimation in Southern China - Lv, Yingjian; Wang, Ping; Huang, Rui; Liang, Xuxia; Wang, Peng; Tan, Jianbin; Chen, Zihui; Dun, Zhongjun; Wang, Jing; Jiang, Qi; Wu, Shixuan; Ling, Haituan; et al. (Journal of bone and mineral research, 2017)
ABSTRACT This study aimed to assess the association between osteoporosis and long‐term environmental Cd exposure through diet in southern China. A total of 1116 subjects from a Cd‐polluted area and a non‐Cd‐polluted area were investigated. All subjects met the criteria of having been living in the investigated area for more than 15 years and lived on a subsistence diet of rice and vegetables grown in that area. Besides bone mineral density, the levels of urinary markers of early renal impairment, such as urinary N‐acetyl‐β‐D‐glucosaminidase (NAG), α1‐microglobulin, β2‐microglobulin, and urinary albumin, were also determined. Urinary Cd concentrations of all studied subjects ranged from 0.21 to 87.31 µg/g creatinine, with a median of 3.97 µg/g creatinine. Multivariate linear regression models indicated a significant negative association of urinary Cd concentrations with bone mineral density. In logistic regression models, both categorical and continuous urinary Cd concentrations were positively associated with osteoporosis. Subjects in the second, third, and fourth quartiles of urinary Cd concentration had greater odds of osteoporosis compared with subjects in the first quartile (odds ratio [OR] = 3.07, 95% confidence interval [CI], 1.77 to 5.33; OR = 4.63, 95% CI, 2.68 to 7.98; OR = 9.15, 95% CI, 5.26 to 15.94, respectively). Additional adjustment for levels of urinary markers did not attenuate the associations. No evidence existed of an interaction between urinary Cd concentration and renal function using levels of urinary markers, and estimated glomerular filtration rate (eGFR). In all subjects, the benchmark dose and benchmark dose lower bound were 1.14 (0.61) and 2.73 (1.83) µg/g creatinine, with benchmark response set at 5% and 10%, respectively. The benchmark dose of urinary Cd was lower in women than in men. This study demonstrated an inverse association between the body burden of Cd and osteoporosis. The toxic effect of Cd on bone may occur in parallel to nephrotoxicity. © 2017 American Society for Bone and Mineral Research.